Sustainable strategies in the luxury business to increase efficiency in reducing carbon footprint - López, Belén; Rangel Pérez, Celia; Fernández, Manuel (Elsevier Inc., 2023)
This research aims to analyse whether a sustainable strategy brings efficiency to the luxury sector in the fight against carbon footprint. Such an aim has been approached by establishing a relationship between the actions implemented in the sector,the carbon footprint as measured by the Intergovernmental Panel on Climate Change methodology,and the market share of the main market operators. The results reveal which actions tend to be efficient in terms of carbon footprint fight,which actions do not,and how concentration or dispersion of main operators has impacted the global carbon footprint in the sector. Consequently,this work explores specific actions that luxury companies take to be economically efficient in their business strategy and to protect the environment. Finally,companies must be efficient and sustainable to contribute to the United Nations’ Sustainable Development Goals outlined in the 2030 Agenda. © 2022 The Author(s)
Keywords: Climate change; CSR; Efficiency; Luxury brands; Strategy; Sustainability; Climate change; CSR; Efficiency; Luxury brands; Strategy; Sustainability; 63 Sociología::6311 Sociología de los asentamientos humanos::6311.02 Sociología ecológica; ODS 4 - Educación de calidad; ODS 2 - Hambre cero; ODS 15 - Vida de ecosistemas terrestres; ODS 12 - Producción y consumo responsables; ODS 13 - Acción por el clima; ODS 14 - Vida submarina